π‐Expanded Carbazoles as Hole‐Selective Self‐Assembled Monolayers for High‐Performance Perovskite Solar Cells - Jiang, Wenlin; Li, Fengzhu; Li, Mingliang; Qi, Feng; Lin, Francis R.; Jen, Alex K.‐Y. (Angewandte Chemie International Edition, 2022)
Carbazole‐derived self‐assembled monolayers (SAMs) are promising hole‐selective materials for inverted perovskite solar cells (PSCs). However, they often possess small dipoles which prohibit them from effectively modulating the workfunction of ITO substrate, limiting the PSC photovoltage. Moreover, their properties can be drastically affected by even subtle structural modifications, undermining the final PSC performance. Here, we designed two carbazole‐derived SAMs, CbzPh and CbzNaph through asymmetric or helical π‐expansion for improved molecular dipole moment and strengthened π‐π interaction. The helical π‐expanded CbzNaph has the largest dipole, forming densely packed and ordered monolayer, facilitated by the highly ordered assembly observed in its π‐scaffold's single crystal. These synergistically modulate the perovskite crystallization atop and tune the ITO workfunction. Consequently, the champion PSC employing CbzNaph showed an excellent 24.1 % efficiency and improved stability. A molecular design strategy is introduced for carbazole‐derived self‐assembled monolayers (SAM) to facilitate dense assembly and tune the indium tinoxide (ITO) workfunction. Through asymmetric or helical π‐expansion, CbzPh and CbzNaph are obtained as efficient hole‐selective layers (HSL) for inverted perovskite solar cells (PSC). Larger molecular dipoles in CbzPh and CbzNaph can better tune the ITO workfunction, whereas the stronger π‐π interactions ensure more ordered and denser SAM assembly.